Circuit Model for Microstrip Array Antenna with Defected Ground Structures for Mutual Coupling Reduction and Beamforming Applications - Subhi, Khalid; Fauziahanim Che Seman; Shipun Anuar Hamzah; Goh Chin Hock; Shaharil Mohd Shah (International Journal of Integrated Engineering, 2021)
A microstrip array antenna (MAA) structure incorporated with an orthogonal I-shaped defected ground structure (OI-DGS) was proposed and investigated and its equivalent circuit was created. Reflection losses were simulated and verified with the proposed circuit model using CST Commercial and AWR Microwave Office software. The optimized S11 parameter of the model was obtained by tuning the dimensions of the microstrip patch elements in the MAA and the lengths and widths of the slots of defected ground structure (DGS). The proposed equivalent circuit is expected to be useful as a model for the DGS design and to study its behavior. Finally, two prototypes of MAA, without and with OI-DGS, were fabricated by the milling technology and tested. The simulated results showed that -5.53 dB mutual coupling reduction and the measured around -3 dB. The simulated results demonstrate that main beam shifted 43Â° while the measured main beam shifted 36Â°.